TILAWATI METHOD IN IMPROVING MEMORIZATION OF AL-QUR'AN AT MUHAMMADIYAH 12 ELEMENTARY SCHOOL IN SURABAYA - Muhammad Hafifulloh Ghoni; Moch. Tolchah; Mahsun Jayadi (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to describe the achievement of students' memorization of the Qur'an, the application of the Tilawati method, and the supporting and inhibiting factors in tahfidz learning at SD Muhammadiyah 12 Surabaya. The background of this study is the success of the tahfidz program in a public elementary school that is not pesantren-based, but targets students' memorization equivalent to pesantren institutions. This research uses a qualitative method with a case study approach. Data collection techniques were conducted through observation, in-depth interviews, and documentation with tahfidz coordinators, tahfidz teachers, students, parents, and munaqisy. The results showed that the Tilawati method proved to be effective in improving student memorization, with a percentage of 70% of students reaching the target of one juz per year, even some were able to exceed up to 14 juz. This success is supported by systematic learning, the use of rost tones, memorization patterns per column, competent tahfidz teacher guidance, a religious school environment, and the existence of a monthly tahfidz boarding program. In addition, the active involvement of parents also supports the students' memorization process. The obstacles faced include the instability of students' motivation to memorize, the influence of gadgets, busy schoolwork, and the limited time and ability of parents to accompany their children. The conclusion of this study confirms that the success of the tahfidz program is highly dependent on the synergy between appropriate learning methods, the role of teachers and schools, and family support. Further research is recommended to evaluate the long-term impact of the Tilawati method on students' character development and academic achievement.